An unusual new species of Canthidium (Coleoptera: Scarabaeidae: Scarabaeinae) from Oaxaca, Mexico - Kohlmann, Bert; Arriaga-Jiménez, Alfonsina; Rös, Matthias (Zootaxa, 2018)
In this paper we describe Canthidium quercetorum new species (Coleoptera: Scarabaeidae: Scarabaeinae), a species that inhabits dry oak forest in the Mexican state of Oaxaca, between 2100 and 2300 m above sea level. Photographs and an illustration of the habitus and a distribution map are provided. The unusual distribution and ecology of this species are discussed. An updated key for the genus in Mexico and the United States of America is also presented.